PRESCRIPTIONS AND DRUGS: UNDERSTANDING THE ROLE OF MEDICATIONS IN HEALTHCARE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the critical role of medications in healthcare, emphasizing their significance in disease management, symptom relief, and overall patient care. It discusses the various types of prescriptions, including acute and chronic medications, and examines the processes involved in prescribing, dispensing, and monitoring drug therapy. The article also highlights the importance of medication adherence, patient education, and the potential risks associated with improper use of medications. Furthermore, it addresses the evolving landscape of pharmaceuticals, including advancements in personalized medicine and the impact of technology on prescription practices. By understanding the multifaceted role of medications, healthcare professionals can enhance treatment outcomes and improve patient quality of life.
Keywords: Medications, Prescriptions, Healthcare, Disease management, Symptom relief, Medication adherence, Patient education